ANALYSIS OF THE IMPLEMENTATION OF THE PEOPLE'S BUSINESS CREDIT (KUR) POLICY IN IMPROVING THE PERFORMANCE OF MSMES IN BITUNG CITY - Ervina Tunas; Wilson Bogar; Steven V. Tarore. (PT. Radja Intercontinental Publishing, 2026)
This study aims to determine, analyze, and describe the disbursement process of People's Business Credit (KUR) and identify determinants in the disbursement process that influence the achievement of the goal of improving MSME performance at the local level, particularly in Bitung City. This study uses a qualitative approach with a case study design. Data collection techniques were carried out through in-depth interviews, observation, and documentation with officials of Bank BRI, the Bitung City Cooperatives and MSMEs Office, and MSME actors. The results show that the technical procedures for KUR distribution based on Coordinating Minister for Economic Affairs Regulation Number 7 of 2024 have been implemented, but there are gaps in understanding at the target group level regarding business criteria, credit history, and document requirements. Determinants that influence the disbursement process include the rigidity of the SLIK/SIKP verification algorithm for micro-consumer credit, rigid top-up procedures with administrative delays, the inactivity of the Integrated Business Service Center (PLUT) due to budget efficiency, and the public perception that KUR is still considered social assistance. These findings suggest the need for revitalization of centralized mentoring functions, procedural flexibility, and increased financial literacy so that KUR truly functions as an instrument for improving business performance.